Comparative Study of Thermochemical Valorization of CCN51 Cocoa Shells: Combustion, Pyrolysis, and Gasification - Cristian Laverde-Albarracín; Juan Félix González; Beatriz Ledesma; Silvia Román-Suero (Applied Sciences)
Cocoa shells (variety CCN51, exclusive from Ecuador) were subjected to different thermochemical processes (combustion, pyrolysis, and gasification) to evaluate their potential for energy production. Pyrolysis was conducted at 500, 600, and 700 °C, yielding solid (35.89–41.27%), liquid (31.13–34.73%), and gas (24.92–32.92%) fractions. The higher heating value (HHV) of the solid phase increased with temperature, reaching 24.97 MJ/kg at 700 °C. Gasification was performed under air flow at 500, 600, and 700 °C, producing synthesis gas with an HHV ranging from 0.89 to 3.36 MJ/m3. The H2 and CO contents in the gas phase increased with temperature, reaching 9.98% and 11.77% at 700 °C, respectively. Combustion analysis, conducted via thermogravimetry coupled with mass spectrometry, revealed efficient volatile release and oxidation patterns. The high potassium content in the ashes (72.02% K2O) may affect slagging behavior but also presents opportunities for agricultural applications. These findings highlight the potential of CCN51 cocoa shells as a sustainable biomass resource, contributing to Ecuador’s green transition and the local circular economy.